Ubiquitous computer aided design: A broken promise or a Sleeping Beauty?. (February 2015) - Horváth, Imre; Vroom, Regine W.
Abstract: As a novel computational approach, ubiquitous computing was emerging at the beginning of the 1980s and has reached a rather mature level by now. It assumes that computing can be available anywhere, anytime and in any context due to technological developments, social demands and calm implementations. Over the years, the opportunities of this computing paradigm have been explored and the benefits have been exploited successfully in many application fields. This survey paper addresses ubiquitous computing from the perspective of enabling computer aided design. The specific objectives of the reported survey are to: (i) give an overall account of the current status of ubiquitous computing and technologies, (ii) cast light on how ubiquitous computing has influenced the development of CAD systems, tools, and methods, and (iii) critically investigate future development opportunities of ubiquitous computing enabled computer aided design. First, the paper discusses the principles and typical technologies of ubiquitous computing. Then, the development and spectrum of the so-called standard computer aided design tasks are analyzed from a computational point of view. Afterwards, the already implemented design enabling functionalities are discussed and some additional functional possibilities are considered. The literature provides evidence that ubiquitous computing has not managed to revolutionize the methodologies or the systems of computer aided design so far, though many researchers intensively studied the affordances and the application possibilities of ubiquitous technologies. One reason is that ubiquitous computing technologies had in the last two decades to compete with other kinds of computational technologies, such as high-capacity computing, high-speed networking, immersive virtual reality, knowledge ontologies, smart software agents, mobile communication, etc., which had a much stronger influence on the development of computer aided design methods and systems. In combination with the rather conservative and conventionalist industrial practice of CAD system development and application, this may explain why the ubiquitous computing revolution remained weak in computer aided design. The literature clearly indicates that application of ubiquitous technologies did not lead to radically new functionalities that could have been exploited by the concerned industries. Consequently, it seems to be possible that computer aided design simply steps over the paradigm of ubiquitous computing and expects new functionalities from the emerging new computing paradigms, such as brain–computer interfacing, cyber–physical computing, biological computing, or quantum computing. Highlights: An overall account of the status of ubiquitous computing and technologies in CAD. Penetration of ubiquitous computing remained insignificant in most applications. Application of ubiquitous technologies did not lead to radically new functionalities. Computer aided design steps over the paradigm of ubiquitous computing. New CAD functionalities expected from the emerging new computer paradigms.